Pelatihan Pembelajaran Cabang Olahraga Bulu Tangkis Pada Siswa Kelas Viii Di Smp Negeri 12 Kota Bengkulu - Dwingki Marta Putra; Tiara Herlina (Jurnal Dehasen Untuk Negeri, 2024)
SMP Negeri 12 Kota Bengkulu Located in Lempuing, at SMP Negeri 12 Kota Bengkulu there are many extracurricular activities, one of the active extracurriculars is badminton which is played every Friday afternoon at exactly 15.30 – 17.30 on the Rangonang field, extracurricular sports are badminton. approximately 23 students participated in badminton, consisting of 9 men and 14 women. The sport of badminton is very popular among students at SMP Negeri 12 Bengkulu City, which means that there are students who are enthusiastic about taking part in the training. Where there are Dehasen University lecturers who are teachers at SMP Negeri 12 Bengkulu City, it will make it easier to carry out service both with the school and students at SMP Negeri 12 Bengkulu City. so that community service was carried out by Dehasen University lecturers with the theme: Badminton Learning Training for Class VIII Students at SMP Negeri 12 Bengkulu City.